Facebook marketing all-in-one for dummies - Porterfield, Amy (--For dummies., 2013)
Great new edition covers what you need to know for successful Facebook marketingFacebook keeps evolving, and so does the social mediasphere. Even if you have a Facebook marketing strategy, have you taken into consideration Pinterest' Spotify' Foursquare' Facebook Marketing All-in-One For Dummies, 2nd Edition does. This detailed resource not only reveals how to create successful Facebook marketing strategies, it also shows you how to incorporate and use the entire social network to its full potential. Covers the tools, techniques, and apps you need to know to create successful Facebook marketing campaignsNine minibooks cover the essentials: Joining the Facebook Marketing Revolution; Claiming Your Presence On Facebook; Adding the Basics; Building, Engaging, Retaining, and Selling; Understanding Facebook Applications; Making Facebook Come Alive; Advanced Facebook Marketing Tactics; Facebook Advertising; Measuring, Monitoring, and AnalyzingExplores the new Timeline design for Pages, changes to Facebook Insights, new apps to incorporate into your strategy, and moreFacebook Marketing All-in-One For Dummies, 2nd Edition is the perfect resource for any marketer who wants to build or refine a social media marketing presence that includes Facebook.